Coverage of policies to improve antimicrobial stewardship in human medicine in low and middle income countries: results from the Global Survey of Experts on Antimicrobial Resistance - Kyaw Zay Ya; Mark J. Lambiris; Gillian A. Levine; Fabrizio Tediosi; Günther Fink (BMC, 2024)
Abstract Background Antimicrobial resistance (AMR) constitutes a major threat to global health. While antimicrobial misuse or overuse is one of the main drivers for AMR, little is known about the extent to which antibiotic misuse is due to a lack of national government-led efforts to enforce rational use in low and middle-income countries (LMICs). Methods To assess antimicrobial stewardship and national implementation measures currently in place for optimizing antimicrobial use and for slowing the spread of AMR, we invited public health experts from 138 LMICs to participate in a Global Survey of Experts on Antimicrobial Resistance (GSEAR). Key coverage measures, as reported by experts, were compared across countries and also juxtaposed with estimates collected in the 2020-21 World Health Organization-organized Tripartite AMR Country Self-Assessment Survey (TrACSS). Results A total of 352 completed surveys from 118 LMICs were analysed. Experts in 67% of the surveyed countries reported a national action plan (NAP) on AMR, 64% reported legislative policies on antimicrobial use, 58% reported national training programs for health professionals, and 10% reported national monitoring systems for antimicrobials. 51% of LMICs had specific targeted policies to limit the sale and use of protected or reserve antibiotics. While 72% of LMICs had prescription requirements for accessing antibiotics, getting antibiotics without a prescription was reported to be possible in practice in 74% of LMICs. On average, country efforts reported in TrACSS were substantially higher than those seen in GSEAR. Conclusions In many LMICs, despite the existence of policies aimed at slowing down the spread of AMR, there are still significant gaps in their implementation and enforcement. Increased national efforts in the areas of enforcement and monitoring of antibiotic use as well as regular monitoring of national efforts are urgently needed to reduce inappropriate antibiotic use in LMICs and to slow the spread of AMR globally.